THE USAGE OF MULTIMEDIA FOR CHILDREN AND ADOLESCENTS IN EDUCATIONAL PROCESS - Lidiia Piskozub (Інтегровані комунікації)
More and more, multimedia in its various types and forms is becoming an integral part of learning for children and children with special educational needs (SEN). After all, multimedia provides ease and visibility of the presented material, develops the skills of full-fledged interaction of children with the help of special tools and high-quality modern software, improves memory, and gives a feeling of enthusiasm for the subject, which is their primary task.